Design and Implementation of a Performance Dashboard for Public Relations at Telkom University: Perancangan dan Implementasi Dashboard Kinerja Bidang Humas Universitas Telkom - Feddy Dea Reskyadita; Hani Nurrahmi; Daris Maulana (NUANSA INFORMATIKA, 2025)
The Public Relations and Analytics (PRA) division at Telkom University faces challenges in managing manual processes and integrating data from diverse sources, hindering efficient reputation management. This study developed PANDA (Public Relations and Analytics Dashboard Application), a web-based system with an interactive performance dashboard to optimize PRA operations. Using the Waterfall methodology, the research encompassed requirements analysis, system design, implementation, and initial evaluation. PANDA integrates real-time key performance indicators (KPIs) such as media coverage, social media engagement, website analytics, and enabling data-driven decision-making. The System Usability Scale (SUS) evaluation resulted in a high score of 82 (categorized as 'Good to Excellent'), demonstrating PANDA's effectiveness in enhancing usability and streamlining operational workflows. The system enhances PR performance monitoring and offers a scalable model for educational institutions.